(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
The cultivation of oyster mushrooms (Pleurotus ostreatus) in Indralaya is insufficient to supply market, due to limited knowledge and cultivation practices among local communities. This field practice aimed to examine the stages, maintenance methods, marketing strategies, and challenges in oyster mushroom cultivation. The research was conducted at Mr. Eko Supandi’s oyster mushroom farm in Payakabung Village, North Indralaya Subdistrict, Ogan Ilir Regency, South Sumatra Province. The case study method was employed. The results revealed that the cultivation process consists of several stages: construction of the mushroom house (kumbung), seed preparation and production, substrate or baglog preparation (including substrate preparation, material mixing and composting, packing, and pasteurization), inoculation, seed incubation for 40–60 days, baglog maintenance, harvesting, and post-harvest handling. Marketing channels include local communities, traditional and modern markets, as well as distributors.